Dewaterability and energy consumption of electro-dewatered sludge near the anode and the cathode during electro-dewatering process. Issue 4 (August 2021) - Sha, Li; Wu, Zhangxiang; Ling, Zichen; Liu, Xingxin; Yu, Xiaoyan; Zhang, Shuting
Abstract: The difference of moisture distribution, physicochemical characteristics, and extracellular polymeric substances (EPS) properties of activated sludge between the anode and the cathode increases gradually during electro-dewatering (EDW) process. However, the dewatering efficiency of the EDW on the electro-dewatered sludge near the anode (ESA) and the electro-dewatered sludge near the cathode (ESC) are unknown. Therefore, the study investigated the dewaterability and energy consumption (EC) of the ESA and the ESC during EDW process, and the dewatering mechanisms related to the variation of sludge properties. Sludge was electro-dewatered to the average moisture content (AMC) of 70% and 60% at 30 V, respectively; then, ESA and ESC were collected and electro-dewatered. The results showed that at 70% AMC, the dewaterability of raw sludge was higher than that of ESA and ESC; compared with the raw sludge and the ESA, the ESC had the lowest EC value at the terminal stage of EDW. At 60% AMC, the ESA was unable to be dewatered, and the EC of ESC increased sharply compared with that at 70% AMC. The moisture at the cathode side of raw sludge and ESC at 60% AMC were difficult to be removed by EDW. Moreover, the higher content of protein (PN) in soluble EPS (S-EPS) and loosely bound EPS (LB-EPS), and a lower value of the α-helix/ (β-sheet + random coil) of ESC could decrease the dewaterability. These results revealed the feasibility of EDW of ESA and ESC, and provided some guidance for low EC operation of the EDW process. Graphical Abstract: ga1 Highlights: The dewaterability and EC of ESA and ESC during EDW were investigated. The EC of ESC at 70% AMC was lower than that of raw sludge and ESA. Moisture at the cathode of sludge at 60% AMC was difficult to be removed by EDW. The highest PN content in S-EPS and LB-EPS of ESC-C hindered the EDW.